2006
DOI: 10.1385/jmn:30:1:55
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptors Containing Subunits α3 and α5 in Rat Nociceptive Dorsal Root Ganglion Neurons

Abstract: Nociceptive primary afferent neurons carry nicotinic acetylcholine receptors (nAChRs). Using RTPCR, mRNAs for all alpha-subunits have been identified in rat dorsal root ganglia (DRG) (Genzen et al., 2001; Lips et al., 2002), but the responses of nociceptive neurons to nicotine are not uniform and the cellular distribution of nAChRs within DRG, in general, and among functionally different subtypes of primary afferent neurons, in particular, are only partially resolved (Rau et al., 2005). These diverse actions m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Changes in nAChR subunit expression and nicotine-evoked current primarily affected the peptidergic, GFRα3-positive DRG neuron subpopulation, which is consistent with findings of Flores and colleagues [14], who showed using in situ hybridization that α3 and β4 are co-expressed in medium-diameter neurons. This observation is also consistent with Spies et al [34] who reported small- to medium-sized neurons express the α3 nAChR subunit. In addition, since ~95% of GFRα3 neurons are TRPV1-positive, the overlap in GFRα3/nAChRα3 labeling is consistent with work of Dussor et al [12], who showed overlap of TRPV1 and nAChRα3 mRNAs, and studies of Roberts et al, and Rau et al, who used patch clamp analysis of isolated neurons to show functional overlap of nAChR and TRPV1 activity [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…Changes in nAChR subunit expression and nicotine-evoked current primarily affected the peptidergic, GFRα3-positive DRG neuron subpopulation, which is consistent with findings of Flores and colleagues [14], who showed using in situ hybridization that α3 and β4 are co-expressed in medium-diameter neurons. This observation is also consistent with Spies et al [34] who reported small- to medium-sized neurons express the α3 nAChR subunit. In addition, since ~95% of GFRα3 neurons are TRPV1-positive, the overlap in GFRα3/nAChRα3 labeling is consistent with work of Dussor et al [12], who showed overlap of TRPV1 and nAChRα3 mRNAs, and studies of Roberts et al, and Rau et al, who used patch clamp analysis of isolated neurons to show functional overlap of nAChR and TRPV1 activity [15,16].…”
Section: Discussionsupporting
confidence: 93%
“…α7 nAChRs may be restricted to C afferents, whereas heteromeric nAChRs are expressed by both C and Aδ afferents (Rau et al, 2005). Dorsal root ganglia (DRG) express a majority of α3β4* and α6β4* and a minority of α3/α6β2* nAChRs (Hone, Meyer, McIntyre, & McIntosh, 2011), and functional studies indicate that around 50% of nociceptive neurons in these ganglia express α3/α6β2-sensitive nAChRs (Spies, Lips, Kurzen, Kummer, & Haberberger, 2006).…”
Section: Nociceptorsmentioning
confidence: 99%
“…Expression sites of α9 and α10 nAChR subunits further include the nasal epithelium and the pars tuberalis of the pituitary gland [16, 18], human and rat urothelium [78, 79], human and rat placenta [80-83], rat heart [84] and dorsal root ganglia [85-87]. Furthermore, α9 (α10 not investigated) is expressed in retina [88], sperm [89] and olfactory bulb [90], whereas α10 is expressed in arteries [91, 92] and rat sympathetic ganglia [93].…”
Section: Expression Pattern Of α9 and α10 Nachr Subunitsmentioning
confidence: 99%